Government Agencies in Uruguay: Characteristics and Autonomy of the Decentralized Administration - Freigedo, Martín; Fuentes, Guillermo; Milanesi, Alejandro; Ramos, Conrado; Ruiz Díaz, Matías (Revista del CLAD Reforma y Democracia, 2022)
The creation of agencies has become a popular trend in the world and in Latin America since the New Public Management reforms. Agencies are organizations with greater levels of autonomy from the center of government, which gives them, in theory, greater independence from political fluctuations while they are capable of being more efficient in the quality and management of their services. This article presents the application in Uruguay of the COBRA (Comparative Public Organization Data Base for Research and Analysis – network) project methodology for characterizing and measuring the levels of autonomy of decentralized public sector agencies. Based on the application of a questionnaire to qualified informants, the study analyzes 56 decentralized entities in Uruguay from 2015 to 2020. Among its main results, it shows that there are no significant differences in terms of autonomy in policy definition or resource management between entities governed by public law and those of non-state type. It also highlights that the largest decentralized entities, both those dedicated to the provision of public welfare services and those of a commercial nature, continue to operate predominantly within the framework of public law and enjoy significant levels of autonomy with respect to the center of government. On the other hand, despite their steady growth, the creation of agencies in Uruguay (or smaller administrative structures governed by or with similar characteristics to those of private law) does not evidence a search for greater managerial autonomy with respect to the organizational formats typical of public law. These institutional formats reflect a pattern of State functioning built on partisan control, negotiations and political co-participation, rather than a logic focused on efficiency or management improvements.
Keywords: Decentralized Administration; Public Sector; New Public Administration; Autonomy; Uruguay